Modeling of an Anoxic/Methanogenic Biofilm: Effect of Ph Calculation Within the Biofilm - Huilinir-Curio, C; Montalvo-Martinez, S (2013)
The models of anoxic/methanogenic processes in biofilm reactors published until now have supposed that pH does not change between the bulk liquid and biofilm. These assumptions are not necessarily valid for processes in reactors with biofilms. The present work studied an anoxic/methanogenic biofilm reactor incorporating the pH variation in both bulk and biofilm. Two dynamic models, one including the calculation of pH throughout the biofilm, were solved numerically and compared with each other. The results showed that the inclusion of a pH algorithm calculation produces different profiles and efficiencies on an anoxic/methanogenic biofilm system. Values of C/N ratio higher than 20 mg TOC/mg NO3-N and values of HRT lower than 4.5 h produce differences of up to 46 % with a traditional model that does not include pH calculation inside the biofilm. Thus, the assumption of a constant pH within the biofilm when using the traditional model does not accurately describe the performance of the system under these conditions, and pH calculation inside the bio-film should be included. © Springer-Verlag Berlin Heidelberg 2013.